Aplikasi Booking Barbershop Online Berbasis Web menggunakan Framework CodeIgniter - Firmansyah, Devie; Purwanto, Heri; Wiharko, Teguh; Purbayanto, Bayu (Masoem University, 2023)
Along with the development of the millennial lifestyle, appearance has become a necessity that is considered very important. Looking clean and attractive to the opposite sex is everyone's dream. But there are also other things that are no less important, especially for men, namely appearance with neat hair styling will add charisma to every man. People today do not want to queue for a long time because there is a long queue. Besides that, the busyness of daily activities makes it difficult for people to set aside time to come directly to the barbershop. Therefore, a web-based online barbershop booking application was created to make it easier for people to trim and style their hair without having to queue at the barbershop. In this application there is a feature to call employees at the barbershop to perform services according to the time and address desired by the customer. The research methodology used is a descriptive approach and the software development uses the prototyping method. The result of this research is an online barbershop booking application that can reduce the number of queues at the barbershop.